(untitled) (European Journal of Pure and Applied Mathematics, 2012)
The notion of singular ideal in a ternary semiring is introduced. The notions of singularÂ ternary semirings and nonsingular ternary semirings are also defined. Some properties of singularÂ ideals in ternary semirings are given. Our results obtained can be used to study some radical classesÂ related to singular ideals.